Evaluation of blended instruction based on network platform in cryptography teaching - Wanqing WU; Ruizhong DU (网络与信息安全学报)
According to the characteristics of cryptography course,a hybrid teaching method was designed through the network platform.In order to get the implementation effect of teaching,the evaluation is made from five aspects:teaching method,teaching content,teaching attitude,teaching environment and comprehensive evaluation.The evaluation results show that students' learning effect is improved after using the blended teaching method.The feedback results suggest that we should constantly optimize the teaching content and teaching methods; improve the ability to control the classroom,guide students to learn; teamwork can improve efficiency and reduce the intensity of teachers.These results provide useful help for further improving the practical teaching of cryptography.